Molecular and phytochemical assessment for some seedy strains of Alamar apricot rootstock under salinity stress. Issue 1 (2nd January 2019) - El-Aziz, M. H. Abd; Mohamed, S. Y.; Magwaid, Hadeer E.
ABSTRACT: The aims of our study were to molecularly assess some seedy strains of Alamar Apricot Rootstock using SCoT and ISSR techniques. In addition, assessment of the expression of P5CS gene with assay of some stress-related phytochemical parameters under salinity stress. These strains were irrigated with salt solution for 6 months from June 2016, only eight strains continued to grow under salinity stress. ISSR and SCoT techniques revealed polymorphic patterns and confirmed to be valid in discriminating these eight strains. SCoT technique was better than ISSRs in assessment for molecular diversity and discrimination capacity for all studied seedy strains. However, a significant positive correlation was found only between distances based on ISSR data and Euclidian distances based on stress-related phytochemical parameters data. These strains showed higher values than control for the studied parameters, specially A3 being the best strain in all parameters, in addition to showing a significantly increase in P5CS gene expression compared to control. Also, A3 was distinguished by a few ISSR unique markers. This, suggesting that, these markers may be used as markers assisted selection in the improvement of salinity tolerance. In addition, the possibility of utilizing this strain through other studies as a source of salinity tolerance in Alamar apricot rootstock.